1997
DOI: 10.1016/s0092-8674(00)80377-3
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome and Low Copy Plasmid Segregation in E. coli: Visual Evidence for Distinct Mechanisms

Abstract: We have investigated DNA segregation in E. coli by inserting multiple lac operator sequences into the chromosome near the origin of replication (oriC), in the hisC gene, a terminus marker, and into plasmids P1 and F. Expression of a GFP-LacI fusion protein allowed visualization of lac operator localization. oriC was shown to be specifically localized at or near the cell poles, and when duplicated, one copy moved to the site of new pole formation near the site of cell division. In contrast, P1 and F localized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

38
417
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(457 citation statements)
references
References 43 publications
38
417
2
Order By: Relevance
“…The events involved in chromosome segregation and partitioning include resolution of chromosome dimers resulting from recombinational crossovers between sister chromosomes, decatenation of interlinked daughter chromosomes, and movement of daughter chromosomes away from each other (43). Recent evidence suggests that bacterial chromosome segregation is an active mitosis-like process and that the origin of replication (oriC) of the E. coli and B. subtilis chromosome has a specific orientation during the cell cycle (9,10,20,44). Thus, in newborn cells oriC is oriented toward a cell pole; after replication of this region, one of the two origins moves rapidly toward the opposite pole of the cell while the termination region remains centrally located (10,44).…”
Section: Discussionmentioning
confidence: 99%
“…The events involved in chromosome segregation and partitioning include resolution of chromosome dimers resulting from recombinational crossovers between sister chromosomes, decatenation of interlinked daughter chromosomes, and movement of daughter chromosomes away from each other (43). Recent evidence suggests that bacterial chromosome segregation is an active mitosis-like process and that the origin of replication (oriC) of the E. coli and B. subtilis chromosome has a specific orientation during the cell cycle (9,10,20,44). Thus, in newborn cells oriC is oriented toward a cell pole; after replication of this region, one of the two origins moves rapidly toward the opposite pole of the cell while the termination region remains centrally located (10,44).…”
Section: Discussionmentioning
confidence: 99%
“…Today, techniques such as fluorescent repressor operator systems 6 and the ParB-GFP fusions parS sequences 7 allow visualization of the location in the cell of specific chromosomal loci to investigate chromosome positioning and dynamics.…”
mentioning
confidence: 99%
“…Although proteins, sites, and mechanisms involved in physical separation (decatenation) of bacterial chromosomes have been characterized, much less is known about the mechanisms governing efficient partitioning to daughter cells (for review, see Hiraga 1992;Wake and Errington 1995). Recent work has shown that the chromosomal region around the origin of replication (oriC) is in a defined orientation for most of the bacterial (B. subtilis and E. coli) cell cycle and that newly replicated oriC regions are rapidly separated from each other (Glaser et al 1997;Gordon et al 1997;Lin et al 1997;Webb et al 1997). The origin regions are found toward the poles of the highly condensed nucleoid body, oriented toward the ends of the cell.…”
mentioning
confidence: 99%
“…The origin regions are found toward the poles of the highly condensed nucleoid body, oriented toward the ends of the cell. The rapid separation and localization of oriC regions indicate the function of a mitotic-like apparatus in prokaryotes (Glaser et al 1997;Gordon et al 1997;Lin et al 1997;Webb et al 1997).…”
mentioning
confidence: 99%